1441. Doses of 13-Valent Conjugated Pneumococcal Vaccine (PCV13) for Patients With Multiple Myeloma (MM). (26th November 2018) - Sun, Hsin-Yun; Cheng, Aristine; Huang, Shang-Yi; Chang, Sui-Yuan; Chen, Yee-Chun; Chang, Shan-Chwen
Abstract: Background: Patients with MM are vulnerable to bacterial infection, especially invasive pneumococcal diseases. Vaccination with one-dose PCV13 is recommended, but their poor immunogenicity was observed. We aimed to assess whether two-dose PCV13 might help. Methods: Patients with MM were randomized to receive one- or two- dose PCV13. The two doses were given 1 month apart. Measurements of antibody to the four most common serotypes 6B, 14, 19F, and 23F pre-vaccination, 1, 3, 6, 9, and 12 months after the last dose of PCV13 were performed. Achievement of significant antibody response was defined as greater than equal to twofold increase in the IgG level. Results: From January 2016 to December 2017, a total of 72 patients were randomized to receive one ( n = 35) or two doses ( n = 37) PCV13. Of all, 31 patients (43%), including one dose in 14 and two doses in 17, had completed 12-month follow-up with a median age of 62 years old (IQR 54–66). Sequential changes of significant antibody responses to serotype 6B, 14, 19F, and 23F during 1-year follow-up in one and two does groups are presented in Figure 1. The proportions of significant antibody responses to serotype 6B, 14, 19F, and 23F after 1-year follow-up were 33.3, 25.0, 41.7, and 41.7% in one dose group and 11.8, 35.3, 29.4, and 23.5% in two-dose group, respectively. Conclusion: Two-dose PCV13 did not provide better immunogenicity to patients with MM. Innovative strategies to improve the immunogenicity of PCV13 in patients with MM are needed. Figure 1: Sequential changes of significant antibody responses to serotype 6B, 14, 19F, and 23F during 1-year follow-up in one- and two-dose groups. Disclosures: All authors: No reported disclosures.